PENGARUH KUALITAS PRODUK, HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN DI HAAGEN-DAZS KOTA KASABLANKA JAKARTA - Ulfa Yastin; Sinthon L Siahaan (LPPM Universitas Asa Indonesia, 2019)
The research was conducted on consumers of Haagen-Dazs located in Kota Kasablanka, South Jakarta. The purpose of the research is to determine how the product quality, price and location able to influence to the consumer’s demand in Haagen-Dazs Kota Kasablanka Jakarta. The data used in this study are primary obtained from quetionnaires randomly given to a sample of 100 consumers Haagen-Dazs Kota Kasablanka with incidental sampling method. The variable in this study is the quality of the product (